2011
DOI: 10.1021/jp201585x
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Cooperative Spin Transition in Iron(II) 2D Coordination Polymers: Room-Temperature Visible Spectroscopic Study

Abstract: For the 2D coordination polymers [Fe(3-Fpy)(2)M(II)(CN)(4)] (M(II) = Ni, Pd, Pt), the pressure-induced spin crossover behavior has been investigated at 298 K by monitoring the distinct optical properties associated with each spin state. Cooperative first-order spin transition characterized by a piezohysteresis loop ca. 0.1 GPa wide was observed for the three derivatives. Application of the mean field regular solution theory has enabled estimation of the cooperative parameter, Γ(p), and the enthalpy, ΔH(HL)(p),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 43 publications
0
38
0
Order By: Relevance
“…Regarding this issue, very few attempts have been noticed to record the (p-T) phase diagram by using various detection techniques such as optical reflectivity [19][20][21][29][30][31], magnetic techniques [15][16][17][18][32][33][34], X-ray and neutron diffraction [35][36][37][38][39]. This lack of data could be explained by the difficulty to obtain small variations in the applied pressure in both loading and unloading processes, at variable temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding this issue, very few attempts have been noticed to record the (p-T) phase diagram by using various detection techniques such as optical reflectivity [19][20][21][29][30][31], magnetic techniques [15][16][17][18][32][33][34], X-ray and neutron diffraction [35][36][37][38][39]. This lack of data could be explained by the difficulty to obtain small variations in the applied pressure in both loading and unloading processes, at variable temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, quantitative optical absorption measurements on crystals can be carried out using a cheap optical microscope and an appropriate bandpass filter. Optical spectroscopy has been used since the onset of SCO research [10,11,16,49,59,132] eight orders of magnitude acceleration of the low-temperature tunnelling process could be evidenced for an external pressure of 2 GPa. We expect that recent ultrafast (fs) optical spectroscopy experiments on SCO samples will be also complemented by measurements under pressure in the near future.…”
Section: Other Detection Methodsmentioning
confidence: 99%
“…Figure 10 shows cyanide-based SCO polymers. Recently, a theoretical study has demonstrated that the changes of the elastic and inelastic forces in the crystal as a function of pressure or temperature determine the behaviour of the spin transition in these polymers [132,148].…”
Section: Compounds With Abrupt Thermal Spin Transition Accompanied Wimentioning
confidence: 99%
“…Fig. 41,42 The spin transitions of the SCO@MCM composites were studied optically under a nitrogen atmosphere to exclude any potential oxidation of the samples in air. 7 Hence, the change in spin state can also be followed by optical reflectance measurements in the solid state.…”
Section: Optical Reflectivity Measurementsmentioning
confidence: 99%